Fetoscopy-guided bipolar cord coagulation in selective fetal reduction with complicated monochorionic diamniotic twins: a prospective cohort study. (12th December 2022) - Tang, Hui R.; Dai, Chen Y.; Li, Jie; Dai, Yi M.; Ru, Tong; Li, Ya L.; Xiao, Xian; Fan, Zhong T.; Hu, Ya L.; Zheng, Ming M.
Abstract: Objective: To assess the feasibility of fetoscopy-guided bipolar umbilical cord coagulation for selective fetal reduction in complicated monochorionic diamniotic (MCDA) twin pregnancies. Methods: MCDA twins undergoing fetoscopy-guided bipolar cord coagulation (BCC) were enrolled prospectively between December 2015 to March 2020 in a fetal medicine center. Results: Twenty-three cases undergoing fetoscopy-guided BCC were finally analyzed, including 11 cases for type 2 selective intrauterine growth restriction, 4 cases for twin–twin transfusion syndrome, and 8 cases for a severe discordant anomaly. The overall survival rate was 78.3% (18/23). Conclusions: Fetoscopy‐guided BCC is effective for selective fetal reduction in complicated monochorionic twin pregnancies.